Education is the antidote: Individual- and community-level effects of maternal education on child immunizations in Nigeria. (September 2018) - Burroway, Rebekah; Hargrove, Andrew
Abstract: Nigeria is an interesting case study because it outperforms other lower middle-income countries in economic development, yet ranks among the lowest in the world in immunization coverage rates. Combining multi-level modeling with spatial data techniques, this study investigates the individual- and community-level factors that influence the likelihood that a child is fully immunized, underscoring the importance of maternal education for improving child health. Drawing on data from the Demographic and Health Surveys and the Global Administrative Areas database, the analysis pools data on children aged 12–24 months across 455 communities. The spatial analysis reveals substantial geographic gaps in immunization coverage across Nigeria, demonstrating that not everyone benefits from the purported benefits of economic growth. Results from the multi-level models indicate that women's education has a robust association with vaccinations at the individual level and at the community level, even net of a variety of other household and community characteristics. The education level of a child's own mother influences the likelihood of being immunized, but above and beyond that, living in a community in which many women are educated also influences that likelihood. This suggests that education has a protective effect on child health not only because more individual women are going to school, but also because everyone benefits from the education and empowerment of women in the community. As broad societal transformations take place, education may shape women's capacity to take advantage of better access to power and resources, resulting in a dispersion effect of expanded women's education on health. Highlights: Immunization rates are very unequal in Nigeria, despite overall economic growth. Community maternal education level affects the likelihood of being immunized. Women's education has a "dispersion" or "spillover" effect on child health. The education effect is only partially mediated by employment, wealth, hospital use.